STT3-dependent PD-L1 accumulation on cancer stem cells promotes immune evasion - Jung-Mao Hsu (Nature Portfolio, 2018)
PD-L1 accumulates on cancer stem cells and favours immune evasion but the mechanism underlying this accumulation are unknown. Here the authors show that epithelial-mesenchymal transition induces glycosylation and stabilisation of PD-L1; antagonising this process renders cancer cells sensitive to anti-Tim3-therapy.